Designing and operating a system of care in behavioral health : solutions to fragmentation in mental health - Koman, Stuart L., 1954-; Keane, Robert J. (New York, NY : Routledge, 2025)
"Solutions to Fragmentation in Behavioral Health Services: Designing and Operating an Integrated System of Care proposes a pathway to combat the current fragmentation of mental health services. Drawing on the authors' 25 years of experience in the private and public sectors, this book develops a constellation of integrated treatment services to provide a cohesive path to recovery for individuals with mental or behavioral disorders. Koman and Keane embrace the request by patients and their families to be "at the table" in making decisions about their care and to influence how this care is provided by professionals and institutions. This is an invaluable reference for mental and behavioral health professionals seeking a better way to provide effective mental health services to clients and their families"--
Keywords: Mental health services; Integrated delivery of health care; PSYCHOLOGY / Applied Psychology; PSYCHOLOGY / Mental Health